2021
DOI: 10.5751/es-12566-260316
|View full text |Cite
|
Sign up to set email alerts
|

Participatory planning for local sustainability guided by the Sustainable Development Goals

Abstract: To achieve the United Nations Sustainable Development Goals (SDGs), actions are required at all global, national, and local scales. To ensure coordination between scales, local actions need to be carefully planned to be aligned with global and national priorities. Local planning for sustainability must be adaptive and heterogeneous but also consistent and driven by the community. We describe an approach to co-create a local sustainability plan using the SDGs for a rural community in southeastern Australia usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…91 Previous studies have suggested frameworks for addressing these challenges through transdisciplinary approaches that can go beyond working with researchers and facilitate public community engagement in pathway development processes. 94,95 Although still a niche field, the growing application 96,97 of a variety of transdisciplinary approaches, such as knowledge co-production (including local, practical, and indigenous knowledge) and participatory processes with stakeholders (i.e., co-designing pathways, local priorities, 10 and plans 98 ) have provided opportunities to advance the local-scale understanding of the SDGs.…”
Section: System Dynamics Modeling For Integrated Assessmentmentioning
confidence: 99%
“…91 Previous studies have suggested frameworks for addressing these challenges through transdisciplinary approaches that can go beyond working with researchers and facilitate public community engagement in pathway development processes. 94,95 Although still a niche field, the growing application 96,97 of a variety of transdisciplinary approaches, such as knowledge co-production (including local, practical, and indigenous knowledge) and participatory processes with stakeholders (i.e., co-designing pathways, local priorities, 10 and plans 98 ) have provided opportunities to advance the local-scale understanding of the SDGs.…”
Section: System Dynamics Modeling For Integrated Assessmentmentioning
confidence: 99%
“…A novel model, recently created by Bibri and Krogstie [39] for data-driven SSC, offers a strategic guide for transformation towards sustainability in the context of big data [39]. Other roadmaps are focused on participatory planning towards SSC development [37] and on participatory planning guided by the Sustainable Development Goals (SGDs) [38], which demonstrates an approach to co-create a local sustainability plan using the SDGs for a rural community aiming to align bottom-up local needs with top-down global goals.…”
Section: Existing Smart (Sustainable) City Roadmapsmentioning
confidence: 99%
“…However, large-scale and global scenarios in reality translate into local changes in human interactions with the environment (Moallemi et al, 2020b). Grassroots solutions led by local communities, cities, and businesses can also make synergies with the aspirations of the higher scales and significantly impact the unfolding of higher-level sustainability scenarios (Bandari et al, 2021;Bennett et al, 2021;Szetey et al, 2021aSzetey et al, , 2021b. This brings new challenges for modelling the cross-scale dynamics of scenarios that can account for both higher spatial and temporal resolutions where policy-making (e.g.…”
Section: Discussionmentioning
confidence: 99%